FUNCTIONAL FEATURES OF THE TECHNICAL DOCUMENTATION CONTROL PROGRAM - Dilshod Baratov; Elmurod Astanaliev (Research Parks Publishing LLC, 2021)
The article describe in more detail these necessary features of the program. Let us proceed to the consideration of the functional features of the client part of the system. Functioning of the client of the automated system of accounting and control of signaling systems. For quick access to information stored in a single database of documents, a search procedure with different parameters is necessary. Let us consider in more detail the main program window, the tab selection window, the signaling device registration window, the device registration selection window